2016
DOI: 10.1155/2016/7062630
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Knowledge, and Acceptance of Haematopoietic Stem Cell Transplantation for Sickle Cell Anaemia in Nigeria

Abstract: Background. Sickle cell anaemia (SCA) is an inherited condition whose clinical manifestations arise from the tendency of haemoglobin to polymerize and deform red blood cells into characteristic sickle shape. Allogeneic bone marrow transplantation offers a cure. The aim of this study was to determine the level of awareness, knowledge, and acceptance of this beneficial procedure in Nigeria. Materials and Methods. This multicentre cross-sectional study was conducted in 7 tertiary hospitals in Nigeria in 2015. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Haematopoietic stem cell transplantation (HSCT) is said to be the only established curative treatment for sickle cell anaemia currently accepted [13]. Clinical trials are still ongoing on the use of Mesenchymal stem cells for the treatment of liver and inflammatory bowel diseases.…”
Section: Stem Cell Application For Treatment Of Some Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematopoietic stem cell transplantation (HSCT) is said to be the only established curative treatment for sickle cell anaemia currently accepted [13]. Clinical trials are still ongoing on the use of Mesenchymal stem cells for the treatment of liver and inflammatory bowel diseases.…”
Section: Stem Cell Application For Treatment Of Some Diseasesmentioning
confidence: 99%
“…In a study done on the awareness of BMT for the treatment of sickle cell anaemia in tertiary health centres across some states in Nigeria, 64.5% of the respondent were aware that BMT can be used this however is low when compared to reports gotten from developed countries [59]. Due to low awareness, getting donors is a great challenge.…”
Section: Awarenessmentioning
confidence: 99%
“…For example, one study conducted in India among engineering students found that none had adequate knowledge about SCT, only 30.9% had moderate knowledge, and the rest had inadequate knowledge. 19 On the other hand, Adediran et al, 20 also found inadequate knowledge about SCT among sickle cell patients. In our study, the inadequate knowledge about HSCT can be linked to a lack of information about HSCT in the curriculum.…”
Section: Correct Responses N (%) Knowledge About the Donor Eligibilitymentioning
confidence: 99%
“…The indirect and direct cost of care are huge. Thus establishing a HSCT unit for allogeneic type of HSCT was a cost effective decision [9]. For low population countries like Maldives and Mauritius the density of HSCT candidates is too less to run a programme perennially.…”
Section: Assessment Of Needmentioning
confidence: 99%